PEMBERIAN KOMPENSASI MEMENGARUHI TERHADAP KINERJA KARYAWAN KONTRAK DI ORGANISASI PUBLIK KOTA BANJARMASIN - Widyanti, Rahmi .; Basuki, Basuki; Lamsah, Lamsah; Anhar, Deli (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
There is a universal awareness on the importance of productivity in improving national welfare. The productivity is an essential factor in maintaining and developing the success of an organization. Thus, that a company can achieve its goals one of which to improve the work productivity, then it is an obligation for the leaders to provide motivation for the employees in the form of compensation.This research is willing to achieve the goals namely (1) to determine the effects of salary, intensive, facility, position promotion and work environment on the work performance of contract employees in public organization at Banjarmasin city either simultaneously or partially (2) to determine the most influential factors on the work performance of contract employees in public organization at Banjarmasin city.In this research, the population is all of the employees in production section contract public organization at Banjarmasin city. There are 130 employees as the research samples. The sample collection technique is by purposive sampling technique. The data analysis tools used in this research are validity, reliability, classical assumption test, multiple regression, determination coefficient and hypothesis testing.Results of the research are (1) There are effects of salary on the employee work performance (2) There are effects of incentive on the employee work performance (4) There are effects of work environment on the employee work performance (5) There are significant effects of salary (X1), incentive (X2) allowances (X3), facility (X4), position promotion (X5) and work environment (X6) simultaneously on the work performance (Y). The salary has the dominant effects on the work performance namely by b1=0,248.